Desenvolvimento de imunoensaios eletroquímicos para determinação de biomarcadores aplicados no diagnóstico de doenças em cultivares - Freitas, Tayane Aguiar (2020)
Citrus production is one of the world’s main agricultural activities, and Brazil is its largest producer. Considering the importance of this culture and its constant growth, some diseases may significantly affect world productivity. The Tristeza disease and the citrus canker, caused by the Citrus tristeza virus (CTV) and Xanthomonas citri subsp. citri (Xcc), respectively, are intensively monitored, since plant eradication is the main form of control. Thus, it is of the extreme interest to develop simple, fast, specific and low-cost analytical procedures for detecting these phytopathogens in the early stages. In this sense, this work proposed the development of electrochemical immunoassays for the determination of CTV capsid protein (CP-CTV) and trehalase (TREA) for the diagnosis of Tristeza disease and citrus canker, respectively. These sandwich-type immunoassays used screen-printed carbon electrodes and magnetic particles with biorecognition elements immobilized on their surface, which allowed the capture, separation, and pre-concentration of the analyte. The first approach was the development of a disposable microfluidic device to detect the CP-CTV protein, based on the redox reaction of hydroquinone/H2O2, that was enzymatically generated from the HRP label. The procedure presented a good linearity (r2 = 0.98), with a linear working range of 2.0 fg mL‒1 to 10.0 pg mL‒1, and a detection limit of 0.3 fg mL‒1. In the second approach, trehalase (TREA) was explored as a potential biomarker for the detection of citrus canker, employing an enzymatic and another non-enzymatic immunoassay. Thus, the enzymatic system used HRP as an electrochemical label, while the non-enzymatic immunoassay used gold nanoparticles for this same function. Comparatively, the two procedures presented good results, in which excellent linearities were obtained for the concentration ranges of 25.0 fg mL‒1 to 10.0 pg mL‒1 and 1.0 ‒ 62.5 pg mL‒1 for the enzymatic and non-enzymatic immunoassay, respectively. Besides, the detection limits for the two systems developed were similar, with values of 19.0 and 16.0 fg mL‒1. The third approach involved an immunosensor for multiplexed determination of CP-CTV and TREA proteins using a microfluidic device. In this multiplexed detection strategy, the use of the alkaline phosphatase enzyme as a label promoted good versatility and selectivity to the procedure when compared to the usual immunoassays. The linear intervals of the calibration curves for CP-CTV and TREA were 0.3 to 5.1 pg mL‒1 and 0.8 to 12.5 pg mL‒1, with detection limits of 0.1 and 0.6 pg mL‒1, respectively. Finally, the first and second approaches were applied to samples of healthy and infected plants, followed by comparison with the ELISA-based procedure, with no significant difference between the methods at the 95% confidence level, which demonstrated the applicability of the strategies. Besides, all devices developed showed good accuracy, high sensitivity, and low cost, hence being viable alternatives for the early detection of these diseases.